Avaliação teórico-experimental da deformação por fluência de concretos auto-adensáveis - Ferraz, A. L. N.; Barbosa, M. P.; Salles, F. M.; Pinto Jr., N. O. (Revista ALCONPAT, 2011)
The performance of self-compacting concretes of different classes – 35 e 55 MPa – were evaluated in relation to deformation under slow loading, basic creep, at ages of 7, 14, 28 and 56 days, and in relation to deformation due to shrinkage by drying. Test of compressive strength, tensile strength and elastic modulus were performed on the composites. The shrinkage results were appropriate, presenting similar curves with deformation values slightly lower for mixtures of water/cement equal to 0,45 (concrete “B”). The deformations under load (creep) were higher in the concretes with higher water/cement ratios and lower elastic moduli (concrete "A"). The more aged elements showed lower values of creep; the creep curves showed better stability in the elements with 28 and 56 days. The values of coefficients calculated as per NBR 6118 (ABNT, 2003) showed good correlation with the coefficients calculated experimentally. Keywords: creep; shrinkage; deformations in concretes; self-compacting concrete.